Media Framing and Policy Legitimacy in Road Safety Governance: Online Discourse on Nepal’s Double Helmet Regulation (2016–2026) - Poudyal, Milan Kumar (International Research Journal of MMC, 2026)
The "Double Helmet" regulation in Nepal that mandates helmet use for both riders and pillion passengers which has become governance issue to contest with digital ecosystem. Nepal hosted more than 5,100 registered online media outlets in mid-2025, that is shifting public policy discourse toward digital journalism. The study used an exploratory sequential mixed-methods for examining online media regulation from 2016 to 2026 that has framed and analyzed its impact on public opinion, policy compliance and institutional legitimacy. Secondary data were drawn from a systematically sampled corpus of 105 news items across 21 major digital portals, complemented with quantitative analysis and 10 in-depth interviews with the stakeholder. Findings of the study has revealed that there is deep structural polarization in media packaging. Beyond routine enforcement spectacles, mainstream digital desks have promoted a "Policy Hack and Import Cartel" frame, linking the mandate to an artificial around 12 billion NPR market expansion across Nepal on import-dependent ecosystem. This commercial framing strongly validated a public defense mechanism of "Symbolic Compliance," in which 60–90% of commuters purchase substandard, uncertified headgear merely to evade administrative traffic fines rather than mitigating medical risk. The study also opined that there is a conversely, textual data significant geographic divergence. Because of the geographical divergence, metropolitan media fueled public cynicism over infrastructure deficits and road networks within regional networks successfully which has been constructed narratives of normative compliance by framing enforcement through community-centric welfare campaigns. Ultimately, this study demonstrates that newly registered Transportation Bill of Nepal (2024) attempts to codify compliance through statutory penalties, public legitimacy remains fractured. Online media serves public arena where road safety is constantly negotiated between corporate skepticism and a critical preventive public health intervention.